Surface sintering of tungsten powder targets designed by electromagnetic discharge: A novel approach for film synthesis in magnetron sputtering - B. Wicher (Materials & Design, 2020)
A three-dimensional (3D) sintering method of bulk magnetron targets has been developed recently. However, the use of bulk target had the following limitations: constrained geometry, limited chemical-phase composition, small size and cost-effectiveness. Thus a novel approach of surface sintering (2D) was arranged by a method of electromagnetic discharge evolution without applying any mechanical press. In the proposed method, the internal energy of pulsed plasma flux (~102.3 J) was dissipated at a tungsten (W) powder interface, therefore providing a form of sintered body with a density of 9.24–14.21 g/cm3 in the crystal structure of (α)-W. The morphology view indicates that, for the most part of sinters, only a subsurface (< 100 nm) was well-consolidated, which was in accordance with an almost fourfold increase in thermal diffusivity there, as showed the results of laser flash analysis. Subsequently, the decrease in mean porosity distribution (Vv) from 42.4% to 27.1% in consolidated surface was confirmed by using the microcomputed tomography (μCT) reconstruction. The (2D) sintered target was then used in the synthesis of pure metallic films by gas injection magnetron sputtering. As a result, a conductive (β)-W phase was recognized (103–405 μΩ cm), giving a promising hope for spintronic device applications.